Association of age‐dependent liver injury and fibrosis with immune cell populations. (26th May 2013) - Collins, Bradley H.; Holzknecht, Zoie E.; Lynn, Kellie A.; Sempowski, Gregory D.; Smith, Catherine C.; Liu, Songling; Parker, William; Rockey, Don C.
Abstract Background & Aims The liver's response to injury is fibrosis, and when chronic, cirrhosis. Age is a critical factor impacting many immune‐mediated processes, potentially including the liver's wounding response to injury. Methods The effects of age on acute and chronic liver injury were evaluated using a carbon tetrachloride model in mice. Lymphocyte and macrophage populations were assessed by flow cytometry and immunohistochemical analysis. Results Acute liver injury was greater in 18‐month‐old (old) mice than in 9‐month‐old (middle‐aged) mice as judged by changes in aminotransferases. Similarly, livers of 18‐month‐old mice had a significantly greater fibrogenic response to injury than did livers of 9‐month‐old mice after chronic injury (assessed by col1α1 mRNA expression, morphometric analysis and hydroxyproline measurement). Interestingly, livers from young mice (6 weeks old) also exhibited an increase in fibrogenesis compared to 9‐month‐old mice, albeit not to the same degree as in old mice. Consistent with a role for macrophages in fibrogenesis, the number of liver macrophages in young and 9‐month‐old mice increased, while in chronically injured livers of 18‐month‐old mice, the number of macrophages was reduced, and was less than in the livers of young and 9‐month‐old injured livers. Conclusions Our data indicate that the fibrogenic response to injury varies substantially with age, and moreover that macrophage recruitment and dynamics may be an important component in differential age‐associated fibrotic disease.